2015
DOI: 10.1186/s13148-015-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA methylation profile of Th1 and Th2 cytokine genes are associated with tolerance acquisition in children with IgE-mediated cow’s milk allergy

Abstract: BackgroundEpigenetic changes in DNA methylation could regulate the expression of several allergy-related genes. We investigated whether tolerance acquisition in children with immunoglobulin E (IgE)-mediated cow’s milk allergy (CMA) is characterized by a specific DNA methylation profile of Th2 (IL-4, IL-5) and Th1 (IL-10, IFN-γ)-associated cytokine genes.ResultsDNA methylation of CpGs in the promoting regions of genes from peripheral blood mononuclear cells and serum level of IL-4, IL-5, IL-10 and INF-γ were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 32 publications
4
73
2
Order By: Relevance
“…Aberrant DNA methylation profiles are associated with the pathogenesis of disease. Initially, DNA methylation was associated with tumor formation and progression [25], but later on, variations in DNA methylation have been associated with other diseases [26, 27] including chronic kidney disease (CKD) [28, 29] and immune-mediated diseases such as rheumatoid arthritis [30] and allergy [31, 32]. In addition, variations in DNA methylation of immune-related genes orchestrate the host immune response after organ transplantation [58].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant DNA methylation profiles are associated with the pathogenesis of disease. Initially, DNA methylation was associated with tumor formation and progression [25], but later on, variations in DNA methylation have been associated with other diseases [26, 27] including chronic kidney disease (CKD) [28, 29] and immune-mediated diseases such as rheumatoid arthritis [30] and allergy [31, 32]. In addition, variations in DNA methylation of immune-related genes orchestrate the host immune response after organ transplantation [58].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from FOXP3 methylation, the DNA methylation level of selected Th1 and Th2 cytokines genes can be used as potential biomarkers in predicting tolerance acquisition. In a clinical trial, it was observed that healthy subjects had different DNA methylation profiles in selected Th1 and Th2 cytokines, such as IL-4 , IL-5 , IL-10 , and IFN-γ , if compared to active cow's milk allergy patients [22]. In this way, DNA methylation analysis was clearly able to separate active cow's milk allergy patients from healthy controls.…”
Section: Clinical Utilitymentioning
confidence: 97%
“…In another study investigating the underlying mechanisms for the development of food allergy, Berni Canani et al [22] assessed the DNA methylation of CpGs in the promoter regions of genes from peripheral blood mononuclear cells as well as the serum levels of IL-4, IL-5, IL-10, and IFN-γ in 40 children. These children were divided into 3 groups: children with active IgE-mediated cow's milk allergy (group 1), children who acquired tolerance to cow's milk proteins (group 2), and healthy children (group 3).…”
Section: Interleukinsmentioning
confidence: 99%
“…Alterations in DNAm play a key role in T-cell differentiation and in maintaining T H 1/T H 2 balance, 1, 2 and thus may offer a potential mechanistic explanation for the natural history of CMA. However, to date, research on the epigenetics of FA, 3 or CMA in particular, 4 has been very limited. Most of the available studies are based on small sample sizes (<60 children), and were not replicated in an independent sample.…”
Section: To the Editormentioning
confidence: 99%